Combining sodium-glucose co-transporter-2 inhibitor with mesenchymal stem cells and brown adipose tissue (BAT) and white adipose tissue (WAT) transplantation to mitigate the progression of diabetic kidney disease: a pre-clinical approach - Stephany Beyerstedt; Marcella L. Franco; Alanah K. G. Carlos; Jaqueline Arjona; Gleice R. Josefi-Rocha; Bruno S. Barbosa; Maria Theresa A. Balby-Rocha; Andrei Furlan da Silva; Tuany Marques Reiter Alves; Melise Oliveira Mariano; Maria Clara Soares Klein; Érika Bevilaqua Rangel (Stem Cell Research & Therapy)
Abstract Introduction The increasing prevalence of Diabetes Mellitus (DM) correlates with a rising incidence of Diabetic Kidney Disease (DKD). DKD, a multifactorial condition, is characterized by activation of the renin–angiotensin–aldosterone system (RAAS), with angiotensin II playing a significant role in podocyte injury. While conventional treatments show potential in mitigating DKD progression, a combination of strategies is required to both impede its development and repair damaged structures. Methods In this study, we explored the brown adipose tissue (BAT) and white adipose tissue (WAT) transplantation, and the use of bone marrow mesenchymal stem cell therapy (BM-MSC) combined with sodium-glucose co-transporter-2 (SGLT2) inhibitor treatment and calorie restriction in the BTBRob/ob model, recognized as a robust representation of DKD featuring hyperglycemia, obesity, time-dependent albuminuria, and histological changes. Results Our primary findings revealed enhanced blood glucose control through combined cell therapy, diminished mesangial matrix expansion, alleviated tissue oxidative stress, preserved podocyte numbers, and an upregulation of podocyte structural markers and components of the RAAS renoprotective axis. Conclusion BM-MSC therapy demonstrates considerable promise as a combined treatment for mitigating DKD progression, with similar findings observed for BAT and WAT transplantation.